Blockchain and cryptocurrencies and Iceland - Svavar Hjaltested 1980- (2021)
This thesis aimed to research and gather information if mining on Blockchain is sustainable and if Blockchain could be used as payment intermediation in Iceland. Interviews were performed with various people with expertise within the scope of the thesis. The relevant sectors were selected, the finance sector, the mining and the data sector, the supervision sector, and the electricity sector in Iceland. Short interviews were conducted while the thesis was written. The results indicate that the Icelandic data centers are using sustainable green energy. However, they are primarily using excess energy, the data centers are trying to get better contracts from the electricity companies, but that process is happening slowly. The same cannot be said for the majority of the world, there the data centers are using sustainable energy, like in Norway and in the Nordic countries. However, data centers in Asia are not using sustainable energy. Nonetheless, the number of data centers using sustainable energy is increasing every year. The mining companies are looking more and more to use sustainable energy, which is often better prized than for example, coal. The development will most likely continue in that direction. When looking at the payment intermediation and if Blockchain will be used to simplify the process of transactions, the short answer is yes. Due to the PSD2 declaration, new parties are coming into the field and these new parties are offering more straightforward, quicker, and cheaper solutions than the banks are offering. The market in Iceland is mostly run by the financial industry regarding payment intermediations and the financial industry has recently invested a lot in new systems that they are not willing to abandon in the near future. However, we can see new parties offering new solutions that today are involved in the existing systems within the financial industry. The financial industry is not willing to give up their hold on the payment intermediation business due to loss of revenues. They will most ...